Resistência de genótipos de feijão-vagem ao ataque de bruquíneos, em condições de laboratório - Bottega, Daline Benites [UNESP]; Rodrigues, Camila Alves [UNESP]; de Jesus, Flavio Goncalves; da Silva, Anderson Goncalves [UNESP]; Peixoto, Nei (Univ Fed Rural Semi-arido-ufersa, 2012)
The aim of this paper was to determine resistance types of snap beans genotypes under infestation of bruchins Zabrotes subfasciatus (Bohemann, 1833) of Acanthoscelides obtectus (Say, 1831) in a no choice and free choice tests. The treatments were arranged in a completely randomized design with four and five replications, respectively. In no choice test, it was evaluated the total number of viable and unviable eggs, dry weight of the consumed food, percentage of emerged insects, weight of insects, longevity of adults and biological cycle of egg to adult. In a free choice test, the number of attracted insects for each genotype and total number of eggs were evaluated. The genotype ARFVI047 presents oviposition non-preference resistance type to Z. subfasciatus. The genotype ARFVI008 presents resistance type of the antibiosis to Z. subfasciatus. The genotypes ARFVI006, ARFVI008 and ARFVI029 present resistance of non-preference for oviposition type to Z. subfasciatus and the genotype HAV 56 black seed presents resistance of non-preference type for feeding of A. obtectus.

Este trabalho teve por objetivo, determinar os tipos de resistência envolvidos em genótipos de feijão-vagem ao ataque dos bruquíneos Zabrotes subfasciatus (Bohemann, 1833) e Acanthoscelides obtectus (Say, 1831) em testes com e sem chance de escolha. Para A. obtectus foram testados os genótipos ARFVI006, ARFVI008, ARFVI012, ARFVI014, ARFVI024, ARFVI029, ARFVI047, ARFVI048, HAV56, ARFVI075 com cinco repetições. Para Z. subfasciatus foram testados oito genótipos, não sendo avaliados ARFVI014 e ARFVI075, com quatro repetições. No teste sem chance de escolha foram amostrados os parâmetros: número de ovos viáveis e inviáveis, massa seca consumida, porcentagem de insetos emergidos, peso de insetos, longevidade de adultos e período de ovo a adulto. Para o teste com chance de escolha, avaliou-se o número de insetos atraídos pelos genótipos e número total de ovos. Com os resultados obtidos, pode-se concluir que o genótipo ARFVI047 apresenta resistência do tipo não-preferência para oviposição a Z. subfasciatus; o genótipo ARFVI008 apresenta resistência do tipo antibiose a Z. subfasciatus e o genótipo HAV 56 apresenta resistência do tipo não-preferência para alimentação a A. obtectus.
Resistance of snap beans genotypes to attack by bruchins, in laboratory conditions
Keywords: Zabrotes subfasciatus; Acanthoscelides obtectus; Phaseolus vulgaris; Plant resistance